2006
DOI: 10.1042/bj20060753
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of inhibition of ferrochelatase by N-methylprotoporphyrin

Abstract: Protoporhyrin IX ferrochelatase catalyses the terminal step of the haem-biosynthetic pathway by inserting ferrous iron into protoporphyrin IX. NMPP (N-methylprotoporphyrin), a transition-state analogue and potent inhibitor of ferrochelatase, is commonly used to induce haem deficiency in mammalian cell cultures. To create ferrochelatase variants with different extents of tolerance towards NMPP and to understand further the mechanism of ferrochelatase inhibition by NMPP, we isolated variants with increased NMPP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…This behavior requires that significant amounts of the EZnD IX complex exist in the steady state and therefore that ZnD IX disassociation is partially rate-limiting. This result is thus in agreement with previous transient kinetic studies using iron (16) and zinc (33,34) as metal ion substrates. This conclusion can be contrasted to previous work with the bovine enzyme (35) where steady-state inhibition studies using both product and alternative substrate demonstrated an ordered mechanism where iron bound first.…”
Section: Discussionsupporting
confidence: 83%
“…This behavior requires that significant amounts of the EZnD IX complex exist in the steady state and therefore that ZnD IX disassociation is partially rate-limiting. This result is thus in agreement with previous transient kinetic studies using iron (16) and zinc (33,34) as metal ion substrates. This conclusion can be contrasted to previous work with the bovine enzyme (35) where steady-state inhibition studies using both product and alternative substrate demonstrated an ordered mechanism where iron bound first.…”
Section: Discussionsupporting
confidence: 83%
“…A pre-steady state burst has recently been observed in the murine ferrochelatase catalyzed insertion of zinc into protoporphyrin IX (27); the transient was used to make a detailed study of binding of the inhibitor N-methyl protoporphyrin. However, rate constants for metal ion insertion in the active site were not determined.…”
Section: Discussionmentioning
confidence: 99%
“…1, 2,3), but there are very few reports of transient kinetics (3,27). Most functional analysis and assessment of the significance of mutated residues has relied on steady-state information.…”
mentioning
confidence: 99%
“…26 The emission at 347 nm from 0.20 μM ferrochelatase excited at 288 nm was monitored as the concentration of dSDP was increased, using a Fluoro-Max-2 fluorimeter (Jobon Yvon Spex). Measurements were carried out on triplicate samples for each condition and enzyme.…”
Section: Fluorescence Titration Measurementsmentioning
confidence: 99%
“…While dSDP is a weak inhibitor of bovine and murine ferrochelatases with K i and k d in the micromolar range, Nmethylprotoporphyrin IX (N-MePP) has K i and k d in the nanomolar range. [24][25][26] The structure of the complex with dSDP reveals for the first time the mechanism of inhibition of ferrochelatase by inhibitors with bulky substituents at positions 2 and 4 of the porphyrin ring. His183 is one of the few invariant residues in the ferrochelatase family.…”
Section: Introductionmentioning
confidence: 99%